2012
DOI: 10.1021/jp304380j
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Nature of Absorption/Adsorption in Nanoporous Polysulfide Sorbents for the Li–S Battery

Abstract: The possibility of achieving high-energy, long-life storage batteries has tremendous scientific and technological significance. A prime example is the Li–S cell, which can offer a 3–5-fold increase in energy density compared with conventional Li-ion cells, at lower cost. Despite significant recent advances, there are challenges to its wide-scale implementation. Upon sulfur reduction, intermediate soluble lithium polysulfides readily diffuse into the electrolyte, causing capacity fading and poor Coulombic effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
355
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 482 publications
(368 citation statements)
references
References 24 publications
10
355
1
Order By: Relevance
“…On the basis of the patterned deposition of polysulphides, the strong bonding between polysulphides and the ITO surface provided an alternative route to enhance the performance of Li-S batteries through controlling nucleation and deposition of solid S/Li 2 S species. This ITO-C hybrid interface design is significantly different from the previously reported work on metal oxide additives to suppress the diffusion of polysulphides, such as mesoporous silica 12 , titania 22 , alumina 43 , Mg 0.6 Ni 0.4 O (ref. 44) and metal-organic frameworks 11 , as we demonstrate the importance of engineering the ITO-C hybrid interface in facilitating the polysulphide deposition.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…On the basis of the patterned deposition of polysulphides, the strong bonding between polysulphides and the ITO surface provided an alternative route to enhance the performance of Li-S batteries through controlling nucleation and deposition of solid S/Li 2 S species. This ITO-C hybrid interface design is significantly different from the previously reported work on metal oxide additives to suppress the diffusion of polysulphides, such as mesoporous silica 12 , titania 22 , alumina 43 , Mg 0.6 Ni 0.4 O (ref. 44) and metal-organic frameworks 11 , as we demonstrate the importance of engineering the ITO-C hybrid interface in facilitating the polysulphide deposition.…”
Section: Discussioncontrasting
confidence: 57%
“…6). Figure 1e shows an SEM image and EDX mapping of an ITO glassy carbon hybrid electrode after one cycle of discharging to 1.7 V and then charging to 2.6 V. Although the nonpolar charging product (sulphur) has higher affinity with carbon compared with ITO 18,22,27 , the S elemental mapping still matched with the ITO mapping, indicating that more sulphur attaches to the ITO surface than to the carbon surface. This patterning distribution of sulphur after charging is related to the strong bonding between polysulphides and ITO.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Mesoporous structures, such as those based on carbon, have been shown to help trap polysulphides owing to their small pore sizes (B3 nm) 20,27 . Moreover, metal oxides such as TiO 2 possess hydrophilic Ti-O groups and surface hydroxyl groups, which are known to bind favourably with polysulphide anions, hence further limiting the extent of polysulphide dissolution 21,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the dissolution of polysulfide could be restrained through rational design of carbon and electrode structures, as well as the strengthened interactions between the electrode materials and the active species. Evers et al [13] suggested that the soluble lithium polysulfides are preferentially adsorbed in the pores of the porous carbon material during the processes of discharging/charging, moreover, the polysulfide dissolving into the electrolyte can be retained effectively in the small mesopores due to its strong adsorption ability and small size effect. Thus, good control of the pore size distribution can help to improve the electrochemical properties of the sulfur electrodes [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%